Study the Optical Properties of Polymer Poly Vinyl Alcohol doped with CuO and Fe2Cl3 Thin films - Ahmed, Ghuzlan Sarhan; Salman, Seham Hassan; Abid, Enase Yaseen (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2016)
In this research we prepared thin films from pure polymer  (polyvinyl alcohol PVA )and doped with CuO with concentration 8% ,and Fe2Cl3 at different concentrations (1,5,8)%.This films were prepared by casting method and placed in Britidish (4cm diameter )with thickness(200Â±5)Î¼m.Through the investigation of(X-ray )diffraction it is found all that the samples have polycrystalline structure .Also we measurement the optical properties from this films such as absorption ,transmittion spectra ,absorption coefficient ,energy gap ,extinction coefficient ,refraction index ,finesse coefficient ,the dielectric constant with two parts the real and the imaginary and the optical conductivity .